2018
DOI: 10.1159/000493294
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Aflatoxin B1 Promotes Influenza Infection and Modulates a Switch in Macrophage Polarization from M1 to M2

Abstract: Background/Aims: Swine influenza virus (SIV) is a major pathogen of both animals and humans. Afatoxin B1 (AFB1) is one of the most common mycotoxins in feed and food. However, the central contribution of AFB1 to SIV infection remains unclear. Methods: Here, TCID50 assays, fluorescence-based quantitative real-time PCR, western blotting, immunofluorescence staining, histopathological examination, flow cytometry and scanning electron microscopy were performed to investigate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…This result was in accordance with the observation of Hendrickse et al long back in 1989 that heroin addicts often experienced rapid progression of HIV infection, while street heroin was often contaminated with aflatoxin and that aflatoxin derivatives were commonly found in the body fluids of the addicts [20]. Recent researches also show that when exposed to a low dose of AFB1, people were more vulnerable to SIV infection and suffered increased severity [21].Another chronic adverse effect of AFB1 is malnutrition and growth impairment. Several observations in developing countries have pointed out the accordance of kwashiorkor occurrence with high AFB1 concentration in sera [22][23][24].…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This result was in accordance with the observation of Hendrickse et al long back in 1989 that heroin addicts often experienced rapid progression of HIV infection, while street heroin was often contaminated with aflatoxin and that aflatoxin derivatives were commonly found in the body fluids of the addicts [20]. Recent researches also show that when exposed to a low dose of AFB1, people were more vulnerable to SIV infection and suffered increased severity [21].Another chronic adverse effect of AFB1 is malnutrition and growth impairment. Several observations in developing countries have pointed out the accordance of kwashiorkor occurrence with high AFB1 concentration in sera [22][23][24].…”
supporting
confidence: 89%
“…This result was in accordance with the observation of Hendrickse et al long back in 1989 that heroin addicts often experienced rapid progression of HIV infection, while street heroin was often contaminated with aflatoxin and that aflatoxin derivatives were commonly found in the body fluids of the addicts [20]. Recent researches also show that when exposed to a low dose of AFB1, people were more vulnerable to SIV infection and suffered increased severity [21].…”
supporting
confidence: 88%
“…Their shift between the classically activated (M1, proinflammatory) and alternatively activated (M2, anti-inflammatory) phenotypes has been recognized as a crucial factor in the initiation, progression, and termination of numerous inflammatory diseases (Zhang et al, 2018) and especially in influenza virus infection (Halstead et al, 2018). Modulation of macrophage polarization has previously been shown to inhibit or promote influenza infection by applying GM-CSF (Sun et al, 2018) or Afatoxin B1 (Han et al, 2019), respectively. In this study, we confirm that the high mortality of infected mice is correlated with an abundant recruitment of macrophages to the lung and a high proportion of M1-polarized macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…HPV detected in the rectal squamous cell carcinoma is associated with the increased macrophage M2 polarization 31 . In addition, the swine influenza virus 32 and rhinovirus 33 can also be involved in the regulation of macrophage conversion from M1 to M2 polarization. Saha et al 34 also found that hepatitis C virus can induce monocytes to differentiate into polarized M2 macrophages, which promotes the activation of stellate cells by TGF-β.…”
Section: Discussionmentioning
confidence: 99%